Chlorella-supplemented diet improves the health of honey bee (Apis mellifera) - Jang, Hyeonjeong; Ghosh, Sampat; Sun, Sukjun; Cheon, Kang Jun; Mohamadzade Namin, Saeed; Jung, Chuleui (Frontiers in Ecology and Evolution, 2022)
Nutritional stress is one of the major factors affecting the health of honey bees. Supplementing the pollen patty with microalgae enhances the protein content of the patty and therefore is supposed to improve bee’s health. The objective of the present study was to investigate the effect of Chlorella as a dietary supplement on the health and physiology of the honey bee (Apis mellifera). We formulated the honey bee feed by supplementing Chlorella sorokiniana, obtained commercially, with commercially available rapeseed pollen patty in different amounts—0.5, 2, 5, and 10%, and the treatment groups were named P0.5, P2, P5, and P10, respectively. Pollen patty was set as a positive control and only 50% sucrose solution (no protein) was set as a negative control. Diets were supplied ad libitum to newly emerged workers in cages; food consumption patterns; longevity; and physiology including the development of the brain in terms of protein (i.e., total amino acids), thorax muscle, fat body mass, and glands (hypopharyngeal and venom); and gene expression of nutrition-related gene vitellogenin (Vg) of honey bee at different points of time of their age were observed. The addition of Chlorella significantly increased the food consumption pattern, longevity, gland development, muscle formation, and Vg gene expression significantly in comparison to only a pollen or sugar diet. However, the response varied depending on the level of Chlorella supplementation. As depicted in most of the cases, P2, that is, the pollen diet with 2% of Chlorella supplement exhibited the best outcome in terms of all the tested parameters. Therefore, based on the results obtained in the present study, we concluded that 2% Chlorella supplementation to pollen patty could enhance the health of honey bees, which in turn improves their performance.